Hepatitis C Therapy in Renal Patients: Who, How, When?. Issue 3 (September 2016) - Isnard Bagnis, Corinne; Cacoub, Patrice
Abstract Renal patients are overexposed to hepatitis C virus (HCV) infection. Hepatitis C virus infection may induce renal disease, i.e., cryoglobulinemic membrano-proliferative glomerulopathy and non-cryoglobulinemic nephropathy. Hepatitis C virus impacts general outcomes in chronic kidney disease, dialysis or transplanted patients. Hepatitis C virus infection is now about to be only part of their medical history thanks to new direct acting antiviral drugs exhibiting as much as over 95% of sustained virological response. All HCV-infected patients potentially can receive the treatment. Control of the virus is associated with better outcomes in all cases, whatever the severity of the hepatic or renal disease. This article focuses on HCV-induced renal diseases, the reciprocal impact of HCV infection on the renal outcome and renal status in liver disease, use of new direct-acting antiviral drugs with dosage adaptations and the most recent safety data.